Organizational, Social, Economic and Financial Management Performance of Cooperatives - Geroso, Princess Jeah Marie; Maguate, Guarin (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to determine the level of organizational, social, economic and financial performance of cooperatives when taken altogether and when grouped according to variables and to determine if there is significant difference on the level of organizational, social, economic and financial performance of cooperatives when grouped according variables. This aims to know whether or not organizational, social, and economic performance of cooperatives significantly predict financial management performance of cooperatives. Descriptive-Quantitative design is used in this study and instrument used was the Cooperative Performance Report Questionnaire together with interview questions which were conducted through face to face interview. Organizational, Social, Economic and Financial Management Performance of Cooperatives in Negros Occidental when taken altogether is excellent, very satisfactory, excellent, and satisfactory, respectively. There is significant difference in the level of organizational performance when grouped according to variables. No significant difference in social performance when grouped according to variables.  No significant differences in economic performance of cooperatives when grouped according to variables.  In financial performance of cooperatives when grouped according to variables a significant difference existed, when grouped as to classification, however, no significant difference existed in financial performance of cooperatives when grouped according to age. Organizational, social, economic performances of cooperatives are predictors of financial performance. There is significant relationship between organizational performance and social performance, organizational performance and economic performance, organizational performance and financial management performance, social performance and economic performance, no significant relationship between social performance and financial management performance, economic performance and financial management performance, respectively. Cooperatives maybe encouraged to sustain excellent organizational, social, economic and financial management performances while very satisfactory and satisfactory performances needs improvement. Programs on the improvement of financial performance of cooperatives may be initiated by cooperatives or by proper authorities’ in-charge. Lastly, close and intensive monitoring of Cooperative performance is recommended.